KEMAMPUAN PENGHAMBATAN RADIKAL BEBAS HAND SANITIZER EKSTRAK METANOL DAUN SEPAT(Mitragynaspeciosa) - Rakhmadhan Niah; Novia Ariani (Jurnal Ilmiah Manuntung, 2020)
Leaves Sepat (Mitragynaspeciosa) is a plant of Kalimantan. These plants are often used traditionally to reduce blood sugar and antibacterial. The effectiveness is related with strong antioxidant activity in flavonoid compounds. Flavonoid compounds work through the mechanism of capturing free radicals, reducing oxidative stress. The purpose of this study was to measure the percentage of free radical inhibition in the hand sanitizer of methanol extract of leaves Sepat (Mitragynaspeciosa). Sample extraction by maceration method using methanol. Qualitative analysis of chemical compounds with certain eluents using Thin Layer Chromatography (TLC). The antioxidant activity test using the DPPH immersion method (1,1-Diphenyl-2-picryl Hidrazil) measured absorption at a wavelength of 517 nm. The largest percentage of free radical inhibition was obtained in a hand sanitizer concentration of 80 ppm, which is 51.07 ppm.